The Impact of eWOM and Social Media Advertising on Perceived Value, Satisfaction, and Behavioral Intentions in a Cinema Festival Context - Lamari, Mohamed; Bouslama, Neji (International Review of Management and Marketing, 2025)
This study investigates the effect of social media advertising and different electronic word-of-mouth (eWOM) dimensions on attendees’ perceived value, satisfaction and behavioral intentions in the context of the Carthage Film Festival in Tunisia. Using a sample of 416 festival visitors selected through purposive sampling, the collected data set was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that social media advertising along with eWOM quality and quantity, significantly and positively affect perceived value. In turn, perceived value positively impacts satisfaction, which subsequently improves behavioral intentions. On the other hand, eWOM credibility does not have a significant effect on perceived value. These findings reveal the differences in the effects of eWOM dimensions in shaping the perceptions of consumers towards a cultural event and offer practical insights for festival organizers, public institutions, sponsors and communication agencies seeking to engage their audience through digital strategies. This study also contributes to the literature by contextualizing the mechanisms of digital influence in an experiential and cultural setting in North Africa.